The Effect of Golden Sea Cucumber (StichopusHermanii) Extract on the Healing Process of the White Rat (Rattus Norvegicus) Indicated by Oral Ulcer– A Literature Review - Dio Rafid Prakoso; Diah Purwaningsari; Sihning E.J.Tehupuring; Wachjudi Kurnia (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background Indonesia is a maritime country that is rich in marine resources. There are many marine resources that can be used as herbal medicine. One of them is the golden sea cucumber which is thought to be used as an alternative medicine to speed up the healing process of oral ulcers. The purpose of this study was to determine the effect of golden sea cucumber extract (Stichopushermanii) on the wound healing process in rats with oral ulcers.Method This research is a descriptive study with a literature review design. The articles used are articles published in international and national journals in the 2015-2020 period and are indexed by Scopus, Thomson Reuters, Web Science, Scimago and Sinta.Result The results of the scoping article show that there are active compounds in golden sea cucumbers, namely glycosaminoglycans that consist of hyaluronic acid, heparin / heparan sulfate (HP / HS), chondroitin sulfate / dermatan sulfate (CS / DS) and keratin sulfate (KS) which can form proinflammatory cytokines to trigger the emergence of immune defense cells and can bind to growth factors such as FGF2, VEGF, TGF-b, which will provide stimulation to accelerate the angiogenesis process, fibroblast ploriferation, endothelial differentiation, epithelial differentiation so as to accelerate the wound healing process.ConclutionThe conclusion of this study is the golden sea cucumber has the potency to accelerate the wound healing process by increasing fibroblast formation, collagen synthesis, endothelial differentiation and epithelial differentiation.